La fisiología de la planta y la productividad del cultivo - Riveros, Guillermo; Rodríguez, Nuvia Stella (International Center for Tropical Agriculture, 2010)
Plant physiology and crop productivity The functioning of the rice plant during different growth stages is analyzed at the individual plant level and as a plant community (crop) and then related to physiological and growth processes that determine yields. In the vegetative phase, processes analyzed were root development, tillering, inhibition or suspension, tillers and yield, and leaf cover. In the reproductive phase, the number of panicles per unit area and the number of spikelets per panicle were analyzed. During the maturation phase, deposits, products, reserves, and lodging were analyzed. Genetic variability is discussed to indicate those traits that can be modified to obtain, for example, increased yields. The effects of the environment on the functioning of the rice plant and crop are also indicated, and the role played by agronomic practices in harmonizing the adaptability of varieties to the environment and the environmental offer of production sites is specified.